An integration framework of resources management and disaster organizational approach for UAE national emergency - Alhammadi, Ali Ahmed (2023)
Natural disasters usually have an impact on both the economy, considering its available resources, as well as the society. Therefore, the Federal Emergency Management Agency (FEMA) has been ensuring an equal distribution of resources and budgeting to enhance the process of preparedness during national emergencies. Though the UAE has been faced with major disasters in the past years, the process of disaster management has been complicated as the NCEMA has had difficulties in ensuring the process for disaster management, preparation, and recovery. Consequently, a lack of quality resource allocation due to management practices and framework causes an increase in wastage, as well as a lack of preparation and recovery. It also affects the community growth with the process of returning the way of life to normalcy, taking more time at a higher cost. Therefore, the objective of this study to propose a new framework that integrate the resource and disaster management approach for national emergencies. This study's target population consisted of staff who use their expertise and expertise in UAE crisis management organizations. Out of 152 respondents, only 139 are useable/valid for analysis by Structural Equation Modelling (PLS-SEM). The results show that all five hypotheses are supported. The contribution of this study increases investment and policymaking. The rate of preparedness during a disaster has been low, affecting the economic growth of the UAE with the resources available not enough for disaster management. This will encourage the NCEMA to profit by global ability and empower the coordination of logical, specialized, and human endeavour to react to crises and catastrophes. Besides that, the framework allows the UAE to ensure the quality allocation of resources, which in turn prepares it and its citizens in case any disaster takes place and enhances different policies to sustain the level of emergency preparedness. Furthermore, building a framework that would allow enhancing the process of resource optimization would enable the federal institutions in the UAE to ensure that their disaster management techniques would be effective in reducing the impact of a national disaster or crisis. Future studies could employ a mixed-method (quantitative and qualitative) approach to overcome any issue of information bias.